A New Perspective on Neolithic Sites in the Dubičiai Microregion Using a GIS Spatial Analysis - Marcinkevičiūtė, Eglė (Archaeologia Lituana, 2017)
The article analyses the Dubičiai microregion, which is distinguished by the abundance and diversity of its Stone Age settlements, and presents the possibilities provided by GIS Spatial Analysis in reconstructing this microregion’s Neolithic landscape, distinguishing conditions that affected the selection of the Stone Age settlement sites, and determining the locations where the greatest possibility exists for the discovery of new, not yet known Neolithic settlements.